Mechanical dispersion combined with global longitudinal strain estimated by three dimensional speckle tracking in patients with ST elevation myocardial infarction - Noriaki Iwahashi; Jin Kirigaya; Masaomi Gohbara; Takeru Abe; Mutsuo Horii; Yohei Hanajima; Noriko Toya; Hironori Takahashi; Hidekuni Kirigaya; Yugo Minamimoto; Yuichiro Kimura; Kozo Okada; et al. (International Journal of Cardiology: Heart & Vasculature, 2022)
Background: The role of left ventricular (LV) mechanical dispersion estimated after an ST elevation acute myocardial infarction (STEMI) remains unclear. Methods: The study participants were 208 consecutive patients (152 men, age = 72 years) presenting with STEMI for the first time who underwent primary percutaneous coronary intervention (PCI) within 12 h of STEMI onset. Within 48 h of PCI (mean = 24 h), 2D and 3D speckle-tracking echocardiography were performed. The global longitudinal strain (GLS) was calculated using 3D (3D-GLS) and 2D (2D-GLS) speckle tracking. Mechanical dispersion was defined using the standard deviation (SD) of the time to regional peak longitudinal strain (LS) for all 16 segments for both 2D-STE and 3D-STE (2D-LS-SD, 3D-LS-SD). Infarct size was estimated by Tc99m-sestamibi as the total area of < 50% of the uptake area at 2 weeks. The patients were followed up for a longer period of time (median118months) and checked for major adverse cardiac events (MACE: cardiac death, heart failure). Results: During follow-up, 55 patients experienced MACE. The cut-off values were determined using receiver operating characteristic curves. The multivariate analysis revealed that a 3D-LS-SD > 56.7 ms was a significant predictor of MACEs (hazard ratio = 1.991, 95% confidence interval 1.033–3.613, p = 0.03), but 2D-LS-SD > 58.1 ms was not an independent predictor of MACEs (hazard ratio = 1.577, 95% confidence interval 0.815–3.042, p = 0.1). Furthermore, the combination of 3D-GLS and 3D-LS-SD had accurate predictability for MACE, as shown by the Kaplan-Meier curves (log rank, χ2 = 94.1, p < 0.0001). Conclusions: LV mechanical dispersion besides 3D-GLS assessed by 3D-STE immediately after PCI can predict long-term prognosis.